Urban Risk-Case Study; Oriental Market Managua - Aguilar, Erasmo José (Universidad Nacional de Ingeniería, 2016)
The East Market Managua -MOM is one of the most important trade centers in Central America . The deterioration and functional and constructive problems it a core Urban Vulnerability . This study was applied Histogram Vulnerability assessment components of the built environment to identify the level of risk and increased risk components.